Chemical Composition of the Essential Oil and Antioxidant Activities, Total Phenol and Flavonoid Content of the Extract of Nepeta pogonosperma - F Khalighi - Sigaroodi; M Ahvazi; H Ebrahimzadeh; N Rahimifard (Institue of Medicinal Plants, ACECR, 2013)
Background: Nepeta pogonosperma Jamzad & Assadi (Labiatae) is one of the endemic Nepeta species in Iran (Alamut region). Flavonoids, iridoids, phenols and dierpenes have previously been reported in some Nepeta species. Genus of Nepeta have essential oil and antioxidant, antimicrobial, insecticidal, anti-inflammatory, antinociceptive and anxiolytic activities and also used in folk medicine because of their expectorant, antiseptic, antitussive, antiasthmatic and febrifuge effects. Objective: The purpose of this study was to evaluate chemical composition of the essential oil and antioxidant activities, total phenol and flavonoid content of the extract of N. pogonosperma in the flowering stage. Methods: Total phenol and flavonoid contents of the species were measured using colorimetric methods. The total antioxidant capacity was determined by the following methods: ABTS and DPPH free-radicals scavenging and ferric reducing/antioxidant power (FRAP). Essential oil was extracted by hydrodistillation and was analyzed by GC and GC/MS. Results: The extract possessed a higher concentration of total phenol than total flavonoid content. Methanol extract showed moderate DPPH scavenging activity (IC50 < 200 μg/ml). Fifty constituents were found representing 95.95% of the essential oil. The main constituents of the essential oil were 1,8-cineole and 4aα,7α,7aα-nepetalactone. Conclusion: The present results demonstrate that N. pogonosperma extract exhibits antioxidant activity and may serve as potential source of natural antioxidants for treatment of some diseases. Further investigations are necessary for chemical characterization of the active compounds and more comprehensive biological assays.